2021
DOI: 10.31248/jasp2021.275
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of scale insects (Hemiptera: Coccomorpha) attacking citrus trees in Machakos, Makueni, Kilifi and Kwale Counties, Kenya

Abstract: Citrus farming is a major source of revenue for large and small-scale farmers in Kenya. Citrus production is confronted with threats from pests and diseases. Surveys of citrus farms in Kilifi, Kwale, Machakos and Makueni counties, Kenya in July/August (dry season) and in November/December (wet season), 2019 were conducted to identify scale insect pests (Hemiptera: Coccomorpha) attacking the trees (Sapindales: Rutaceae), and their related biota. A total of 22 scale insect species belonging to four families, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Nevertheless, the results show that this habitat seems to be suboptimal, due to a significantly smaller number of spiderlings; 40 % of burrows (n= 26) were smaller than 5 mm. Several studies have reported relatively high diversity and abundance of arthropods in citric orchards from all over the world (Deshmukh & Chaudhari, 2016;Gama, 2017;Michael et al, 2021), and especially the patches. These ground edges can be almost vertical and higher, like in an abandoned land at the industrial area of Daimús (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results show that this habitat seems to be suboptimal, due to a significantly smaller number of spiderlings; 40 % of burrows (n= 26) were smaller than 5 mm. Several studies have reported relatively high diversity and abundance of arthropods in citric orchards from all over the world (Deshmukh & Chaudhari, 2016;Gama, 2017;Michael et al, 2021), and especially the patches. These ground edges can be almost vertical and higher, like in an abandoned land at the industrial area of Daimús (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…solenopsis . Information is also reported on Parlatoria pergandii and P. ziziphi which had been reported from Kenya earlier this year (Githae et al, 2021). Some of the above species were damaging crops.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…Comments. This record was mentioned by Githae et al (2021), based on a single specimen identified by the last author. The area of origin of chaff scale is uncertain, but it is not native to Africa.…”
Section: *Parlatoria Pergandii Comstock Chaff Scalementioning
confidence: 99%
See 2 more Smart Citations